Myelodysplastický syndrom--klasifikace, prognóza a lécba nemocných - Cermák, J; Michalová, K; Vítek, A (Casopis lekaru ceskych, 2002)
BACKGROUND: The impact of classification, prognostic factors and treatment on survival and rate of leukemic transformation was analysed in 197 patients with primary myelodysplastic syndrome (MDS) treated in the Institute of Hematology and Blood Transfusion in the years 1980-2000. METHODS AND RESULTS: The patients were classified according to the FAB criteria and divided into risk groups according to the International Prognostic Scoring System (IPSS). A separate evaluation of 34 patients who underwent stem cell transplantation and of 163 of those not transplanted was performed. Median survival of not transplanted patients with RAEB (10.0 months) and RAEB-T (12.0 months) was significantly shorter than survival of RA (62.4 months) and RARS (48.1 months, P < 0.001) patients as well as survival of patients included in intermediate II. (13.8 months) and high (10.8 months) risk subgroups when compared to those with low (74.9 months) and intermediate I. risk (56.0 months, P < 0.001). A similar difference was observed in percentage of patients evolving towards acute leukemia and in estimated 3 years survival (EFS). EFS of RA patients was 57% in contrast to 4% in RAEB-T group (P < 0.001) in the same way, EFS in low risk subgroup was 79% vs. 3% in high risk patients (P < 0.001). Chemotherapy alone did not significantly affect median survival of patients with advanced MDS when compared with supportive care. On the contrary, median survival of transplanted patients with RAEB and RAEB-T was 38.4 months in comparison to 11.5 months in those not transplanted (P < 0.001) and 36.8 months vs. 12.0 months in transplanted and not transplanted patients with intermediate II. and high risk (P = 0.05). The difference in survival between transplanted and not transplanted patients with RA and in patients in low and intermediate I. risk subgroups was not statistically significant. CONCLUSIONS: We confirmed an adverse effect of excess of blasts on prognosis of patients with primary MDS. Stem cell transplantation had a significant beneficial effect on survival of patients with RAEB or RAEB-T as well as of patients included in intermediate II. or high risk subgroups. The impact of stem cell transplantation on survival of patients with RA or with low or intermediate I. risk was not significant. Therefore, further criteria should be taken in account for indication of stem cell transplantation in these subgroups of patients.
Keywords: myelodysplastické syndromy; rizikové faktory; Stem Cell Transplantation; Leukemia; Myelodysplastic Syndromes; leukemie; Humans; lidé; Prognosis; prognóza; transplantace kmenových buněk; Risk Factors